Relative growth, morphological sexual maturity, and size of Macrobrachium amazonicum (Heller 1862) (Crustacea, Decapoda, Palaemonidae) in a population with an entirely freshwater life cycle - Pantaleao, J. A. F. [UNESP]; Hirose, G. L.; Costa, Rogério Caetano da [UNESP] (Int Science Services/balaban Publishers, 2012)
The objective of this study was to estimate the size of morphological sexual maturity based on the study of relative growth, to determine the maximum size of individuals, and to determine if there are different morphotypes of males in a population of Macrobrachium amazonicum with an entirely freshwater life cycle. Collections were made monthly, with the use of a net, from September 2006 through August 2007. In each individual, the following structures were measured: carapace length (CL, in mm), width of the second pleuron (PlL, mm), length of the carpus (CaL, mm), and length of the propodus (PrL, mm). Relative growth was analyzed by observing the change in growth patterns of certain parts of the body in relation to the independent variable CL. The maximum sizes found were 8.5 and 11.4 mm CL for males and females, respectively. The morphometric variables: length of the carpus (CL x CaL) for males, and width of the second pleuron (CL x PlL) for females gave the best estimates for the size at maturation, which was 4.26 mm CL for males and 5.39 mm CL for females. The growth pattern in the different stages and the beginning of differential growth seemed to be closely related to reproductive aspects. No indices were found that separated the males into four different morphotypes, as proposed in the literature for coastal or artificially farmed populations. Only the male morphotype termed translucent claw was found in this population. The different morphological patterns in different regions are probably explained by ecological differences in the environments inhabited by these groups, principally in the availability of nutrients and the salinity in which the larvae develop.
Keywords: prawn; morphotype; Caridea; allometry; Tiete River